2014
DOI: 10.1037/a0035566
|View full text |Cite
|
Sign up to set email alerts
|

Examining the factor structures of the Five Facet Mindfulness Questionnaire and the Self-Compassion Scale.

Abstract: The Five Facet Mindfulness Questionnaire (FFMQ; Baer, Smith, Hopkins, Krietemeyer, & Toney, 2006) and the Self-Compassion Scale (SCS; Neff, 2003) are widely used measures of mindfulness and self-compassion in mindfulness-based intervention research. The psychometric properties of the FFMQ and the SCS need to be independently replicated in community samples and relevant clinical samples to support their use. Our primary aim was to establish the factor structures of the FFMQ and SCS in individuals with recurrent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
217
2
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(251 citation statements)
references
References 56 publications
22
217
2
4
Order By: Relevance
“…Finally, SCS-POS and self-esteem both exhibited a protective function in the context of depressive symptoms in children and adolescents. Our finding that the positive and negative subscales formed two nearly orthogonal factors was consistent with emerging research questioning the total score on the SCS even in adult populations (Armstrong et al, 2015;Lopez et al, 2015;Petrocchi et al, 2014;Williams et al, 2014). In the current study, the positivelyworded items comprising the self-kindness, common humanity, and mindfulness subscales of the SCS adhered as SCS-POS, and the negatively-worded items comprising the self-judgment, isolation, and over-identification subscales adhered as SCS-NEG.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Finally, SCS-POS and self-esteem both exhibited a protective function in the context of depressive symptoms in children and adolescents. Our finding that the positive and negative subscales formed two nearly orthogonal factors was consistent with emerging research questioning the total score on the SCS even in adult populations (Armstrong et al, 2015;Lopez et al, 2015;Petrocchi et al, 2014;Williams et al, 2014). In the current study, the positivelyworded items comprising the self-kindness, common humanity, and mindfulness subscales of the SCS adhered as SCS-POS, and the negatively-worded items comprising the self-judgment, isolation, and over-identification subscales adhered as SCS-NEG.…”
Section: Discussionsupporting
confidence: 78%
“…The use of total scores on the SCS is the most common scoring method (Macbeth & Gumley, 2012). However, recent factor-analytic studies (Armstrong et al, 2015;Lopez et al, 2015;Petrocchi, Ottaviani, & Couyoumdjian, 2013;Williams, Dalgleish, Karl, & Kuyken, 2014) failed to replicate the factor structure reported by Neff (2003); none of the four studies found support for a single higher-order self-compassion factor. Armstrong et al (2015) and Lopez et al (2015) suggested that calculating separate scores for positively-and negatively-worded items was preferable to a single total score.…”
Section: Evidence For Beneficial Effects Of Self-compassionmentioning
confidence: 80%
“…In the present study, the correlation between observing and the NAS was also the lowest (in both samples) among FFMQ facets. This finding is not surprising bearing in mind some recent studies (e.g., Desrosiers et al 2014;Williams et al 2014). For instance, Williams et al (2014) found that in both an unspecified community adult sample and a clinical sample, the observing facet did not load significantly onto an overarching mindfulness factor, whereas the other four FFMQ facets did.…”
Section: Discussionmentioning
confidence: 59%
“…Similar concerns regarding the Observing subscale were also reported by other authors (e.g. Curtiss and Klemanski 2014;Williams et al 2014). To account for this uncertainty in addition to five-factor models we also considered fourfactor models which excluded the items associated with the Observing factor.…”
Section: Confirmatory Factor Analyses For Self-report Measuresmentioning
confidence: 80%